Evaluación de la posición cráneo cervical y su relación con los diferentes biotipos faciales, en pacientes atendidos en la clínica de ortodoncia de la Universidad de las Américas - Sarango Pintado, Jonathan Alejandro (2018)
Introduction: The aim of this investigation was to evaluate in the different facial biotypes (brachifacial, mesofacial, dolichofacial), the cervical skull position by means of the cephalometric tracing proposed by Rocabado, to establish similar and normo dependent characteristics for each biotype. Materials and Methods: The sample consisted of 90 lateral radiographs, (56 women and 34 men), with ages between 16 and 31 years, which were divided into three groups (dolichofacial, mesofacial and brachifacial) according to the facial biotype by Vert of Rickets. The cervical cranial angle formed by OP and PMG, the hyoid triangle formed by a perpendicular to the C3-RGn plane passing through H, and the suboccipital space the distance between the base of the occipital and the posterior arch of the atlas. Results: No statistically significant differences were observed when comparing the three cephalometric measures with the facial patterns. In relation to the hyoid triangle, it was evidenced that the highest values corresponded to dolichofacial biotypes of 5.8 mm and the low measurements for the brachifacial biotype with 5 mm, however they were not statistically significant (p = 0.9). The value of the cervical cranial angle did not present statistically significant differences (p = 0.069), it was observed that the measurements between the dolichofacial and brachifacial groups showed a tendency to locate at the extremes of the normal values the dolichofacial low angles (91.7 ° - 97.2 °), intermediate mesofacial (94.9 ° -99.9 °) and high brachifacial (98.9 ° -111 °). The suboccipital space in the three groups was observed within the values, no statistically significant differences (p = 0.548). Conclusions: Similar or normo dependent characteristics are not presented for each biotype, so there is no association between the cranial cervical posture and the facial biotypes.